Morphological spectrum of lesions in renal biopsies with diagnostic role of Immunofluorescence: A study in a tertiary care centre - Venkatesh, Veenaa; Malaichamy, Vinuta; K, Vasanthan M (Annals of Pathology and Laboratory Medicine, 2019)
Background: Renal diseases are common causes of morbidity in clinical practice and their incidence is on rise. Glomerulonephritis constitutes nearly 60% of all non-surgical renal diseases and accounts for a substantial number of cases of end stage renal disease. Objectives: This study was done to analyse the histomorphology of renal diseases. Specific immunofluorescence patterns were also studied as an aid to diagnose various lesions. Materials and methods: This study was done for a period of six months between January 2017 and June 2017. A total of 30 renal biopsies were received in the Department of Pathology, Coimbatore Medical College, Coimbatore. The tissues were subjected to light microscopic examination and immunofluorescence studies. Results: Among the total 30 renal biopsies, the most common age group affected was between 31 years and 40 years. The most common age group affected was between 31 years to 40 years. Females (51.72%) were slightly more affected than males (48.27%). Out of 30 cases, 23 (79.31%) showed primary glomerular lesions, 5 (17.24%) showed secondary glomerular lesion and 2 (3.45%) showed tubulointerstitial nephritis. Diffuse proliferative glomerulonephritis was the most common primary glomerular lesion with a total of 6 out of 30 cases (22.41%). Lupus nephritis was the most common secondary glomerular lesion with a total of 4 out of 30 cases (12.07%). Immunofluorescence studies showed positivity in 21 patients accounting for 72.41%. The predominant pattern was granular glomerular basement membrane which was noted in 9 patients (31.03%). The diagnostic utility of IF was noted in 2 cases (6.90%) whose diagnoses included IgA nephropathy and C1q nephropathy. The IF studies helped in modification of the final diagnosis in 1 case (1.72%) whose final diagnosis was lupus nephritis class I. Conclusion: Immunofluorescence studies have complemented the clinical, histomorphological findings in patients both in primary and secondary glomerular diseases. However, it was even more of diagnostic importance in 5 patients including IgA nephropathy, C1q nephropathy and Lupus nephritis class I where a confident diagnosis could be rendered only because of availability of immunofluorescence studies. Hence, immunofluorescence studies when combined with histomorphologic findings by light microscopy, clinical, biochemical and serological markers can yield a better and precise diagnosis.